Effect of partial and total replacement of fishmeal by soybean meal in feed on growth and gut performance of Penaeus vannamei - Chanadda Kasamechotchung; Natthinee Munkongwongsiri; Pichet Plaipetch; Kanokwan Lertsiri; Siripong Thitamadee; Rapeepun Vanichviriyakit; Siriwan Khidprasert; Kallaya Sritunyalucksana; Felipe Nobre Façanha; Thanapong Kruangkum (Scientific Reports)
Abstract This study evaluated the growth and gut performance of shrimp fed three isonitrogenous diets (37% crude protein) with varying inclusions of fish meal (FM) and soybean meal (SBM): F1 (27.5% FM), F2 (10% FM + 23.5% SBM), and F3 (38% SBM). Over a 28-day period, feed intake, feed conversion ratio (FCR), and survival rates showed no significant differences among the groups. However, shrimp fed F2 and F3 exhibited significantly higher weight gain and average daily growth (ADG) compared to those fed F1 (P < 0.05). Gut performance analysis revealed that F3 consistently had the highest gut passage time (GPT), while F1 had the lowest. By day 28, shrimp fed F2 displayed elevated gut retention time (GRT). F1-fed shrimp showed a high gut passage rate (GPR), whereas F3-fed shrimp had a low GPR until day 21, with differences becoming negligible by day 28. Histological examination of the hepatopancreas revealed an increased R-cell population in shrimp fed F3. These findings highlight the adaptability of shrimp to different dietary compositions and underscore the importance of considering multiple factors when assessing the impacts of feed on growth and physiology.